Longitudinal assessment of cerebral perfusion and vascular response to hypoventilation in a bigenic mouse model of Alzheimer's disease with amyloid and tau pathology. (29th November 2018) - Govaerts, Kristof; Lechat, Benoit; Struys, Tom; Kremer, Anna; Borghgraef, Peter; Van Leuven, Fred; Himmelreich, Uwe; Dresselaers, Tom
Abstract : Alzheimer's disease is the most common neurodegenerative disease, and many patients also present with vascular dysfunction. In this study, we aimed to assess cerebral blood flow (CBF) and cerebrovascular response (CVR) as early, pre‐symptomatic (3 months of age), imaging markers in a bigenic model of Alzheimer's disease (APP.V717IxTau.P301L, biAT) and in the monogenic parental strains. We further developed our previously published combination of pulsed arterial spin labeling perfusion MRI and hypo‐ventilation paradigm, which allows weaning of the mice from the ventilator. Furthermore, the commonly used isoflurane anesthesia induces vasodilation and is thereby inherently a vascular challenge. We therefore assessed perfusion differences in the mouse models under free‐breathing isoflurane conditions. We report (i) that we can determine CBF and hypoventilation‐based CVR under ketamine/midazolam anesthesia and wean mice from the ventilator, making it a valuable tool for assessment of CBF and CVR in mice, (ii) that biAT mice exhibit lower cortical CBF than wild‐type mice at age 3 months, (iii) that CVR was increased in both biAT and APP.V717I mice but not in Tau.P301L mice, identifying the APP genotype as a strong influencer of brain CVR and (iv) that perfusion differences at baseline are masked by the widely used isoflurane anesthesia. Abstract : Using a novel ventilation paradigm that allows for longitudinal repeated measurements, we quantified cerebral blood flow and cerebrovascular response (CVR) in APP.V717IxTau.P301L and wild‐type mice. As illustrated in the accompanying figure, we found that CVR can be a sensitive and relevant readout in the follow‐up of transgenic mouse models of Alzheimer's disease.